Halal Logo Verification Device - Shayfull Zamree, Abd. Rahim; Abdul Rahman, Mohd. Saad, Prof. Madya; Mohd. Azaman, Md. Deros; Mohd Sazli, Saad; Muhamad Farizuan, Rosli (Malaysian Invention & Design Society (MINDS), 2010)
Shayfull Zamree Abd. Rahim and his team won silver at 21st International Invention, Innovation and Technology Exhibition (ITEX) 2010, 14th - 16th May 2010 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.